THE APPROPRIATENESS OF PPI PRESCRIPTION IN A GENERAL MEDICAL COHORT. (8th June 2013) - Moran, N; Jones, E; O'Toole, A; Patchett, S; Harewood, G; Murray, F
Abstract : Introduction: Proton pump inhibitors (PPIs) are one of the most commonly prescribed groups of drug in Ireland, and at great expense. In addition PPIs are associated with side effects. Anecdotally, many patients receive regular PPI treatment for poorly defined reasons and for conditions where PPIs have not been shown to be of benefit. Aims/Background: To assess practices surrounding PPI prescription in acute medical admissions in a tertiary referral centre. Method: In the emergency department, we obtained details of all non-elective admissions during one week from 6th–10th February 2013. We reviewed admission notes to document PPI prescription prior to admission and questioned patients as to whether they knew the duration and indication of their PPI treatment. Results: In total, 102 patients were included, 54 female (53%) and 48 male (47%). The median age was 67 (range 19–88 years). 35.4 % (n=36) were on a PPI on admission. The indication for PPI treatment was documented in 8.3 % of patients. 7.8 % (n=8) were commenced on a PPI on admission. Following patient interviews, 35% (n=12) identified a reason for ongoing PPI use. 65% (n=24) were unclear as to why they were taking a PPI regularly. Indications included GI protection and subjective symptoms of dyspepsia. Conclusion: As PPI use has become more widespread, and in particular with the recent advent of OTC formulations, doctors are less likely to question the original indication for patients' prescription. In fact, patients themselves are often unaware of why they are taking these particular medications.